Recombinant human activated protein C upregulates cyclooxygenase-2 expression in endothelial cells via binding to endothelial cell protein C receptor and activation of protease-activated receptor-1 - Brückmann, Martina; Horn, Sarah; Lang, Siegfried; Fukudome, Kenji; Schulze Nahrup, Adriane; Hoffmann, Ursula; Kaden, Jens; Borggrefe, Martin; Haase, Karl Konstantin; Huhle, Günter (Thrombosis and haemostasis, 2005)
Prostacyclin (PGI2) has beneficial cytoprotective properties, is a potent inhibitor of platelet aggregation and has been reported to improve microcirculatory blood flow during sepsis. The formation of PGI2 in response to proinflammatory cytokines is catalysed by the inducible cyclooxygenase (COX) isoform COX-2. Recombinant human activated protein C (rhAPC, drotrecogin alfa (activated)) was shown to have multiple biological activities in vitro and to promote resolution of organ dysfunction in septic patients. Whether rhAPC exerts its beneficial effects by modulating prostanoid generation is unknown up to now. It was therefore the aim of the study to examine the in vitro effect of rhAPC on COX-2-mRNA-expression and PGI2 release from human umbilical vein endothelial cells (HUVEC). We found that rhAPC, at supra-therapeutical concentrations (500ng/ml-20μg/ ml), upregulated the amount of COX-2-mRNA in HUVEC at t=3-9h and caused a time- and dose-dependent release of 6-keto PGF1α, the stable hydrolysis product of prostacyclin. RhAPC further increased the stimulating effect of tumor necrosis factor-α (TNF-α) and thrombin on COX-2-mRNA-levels. Transcript levels of cyclooxygenase-1 (COX-1) and prostagland-in I2 synthase, however, were unaffected by the stimulation with rhAPC or thrombin. The upregulatory effect on COX2-mRNA levels was specific for rhAPC since the zymogen protein C in equimolar concentrations had no effect on COX-2-mRNA-levels or 6keto PGF1α-release. Western Blot analysis revealed an increase of COX-2-protein content in HUVEC after treatment with rhAPC. As shown by experiments using monoclonal antibodies against the thrombin receptor PAR-1 (mAb=ATAP2) and against the endothelial protein C receptor (EPCR; mAb=RCR-252), the effect of rhAPC on COX-2-mRNA up-regulation was mediated by binding to the EPCR-receptor and signaling via PAR-1. These results demonstrate that induction of COX-2-expression is an important response of HUVEC to stimulation with rhAPC and may represent a new molecular mechanism, by which rhAPC promotes upregulation of prostanoid production in human endothelium.
Elektronische Reproduktion der Druck-Ausgabe
Publikationsdatum: 14. Dezember 2017 (online)
Gesehen am 27.06.2022